Massive surge of mRNA expression of clonal B-cell receptor in patients with COVID-19. Issue 8 (August 2021) - Funakoshi, Yohei; Ohji, Goh; Yakushijin, Kimikazu; Ebisawa, Kei; Arakawa, Yu; Saegusa, Jun; Matsumoto, Hisayuki; Imanishi, Takamitsu; Fukuda, Eriko; Matsutani, Takaji; Mori, Yasuko; Iwata, Kentaro; et al.
Abstract: Background: Antibody production is one of the primary mechanisms for recovery from coronavirus disease 2019 (COVID-19). It is speculated that massive clonal expansion of B cells, which can produce clinically meaningful neutralizing antibodies, occurs in patients who recover on the timing of acquiring adaptive immunity. Methods: To evaluate fluctuations in clonal B cells and the size of the clones, we chronologically assessed the B-cell receptor (BCR) repertoire in three patients with COVID-19 who recovered around 10 days after symptom onset. Results: We focused on the three dominant clonotypes (top 3) in each individual. The percentage frequencies of the top 3 clonotypes increased rapidly and accounted for 27.8 % on day 9 in patient 1, 10.4 % on day 12 in patient 2, and 10.8 % on day 11 in patient 3, respectively. The frequencies of these top 3 clonotypes rapidly decreased as the patients' clinical symptoms improved. Furthermore, BCR network analysis revealed that accumulation of clusters composed of similar complementarity-determining region 3 (CDR3) sequences were rapidly formed, grew, and reached their maximum size around 10 days after symptom onset. Conclusions: BCR repertoire analysis revealed that a massive surge of some unique BCRs occurs during the acquisition of adaptive immunity and recovery. The peaks were more prominent than expected. These results provide insight into the important role of BCRs in the recovery from COVID-19 and raise the possibility of developing neutralizing antibodies as COVID-19 immunotherapy. Abstract : Coronavirus disease 2019; Severe acute respiratory syndrome coronavirus 2; B-cell receptor; Repertoire assay.